Implementation of Sugeno Fuzzy Logic Method as an Automatic Humidity and Moisture Control System in Terrarium - Maulana Cahyani, Dani Syaban; Ikhsan, Muhammad (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2024)
A terrarium is a mini ecosystem that requires precise humidity control to ensure plant growth and the survival of animals within it. However, manual humidity control is difficult to implement consistently, especially if the external environment changes. This problem can be overcome by implementing an automatic system based on Sugeno fuzzy logic. This research aims to design and implement an automatic system that is able to control terrarium humidity dynamically using a fuzzy logic approach. This system is designed using humidity sensor data as input which is then processed through Sugeno fuzzy logic to determine appropriate control actions. The method used involves modeling input humidity and temperature sensors, determining fuzzy rules, and defuzzification using the Sugeno method to regulate the automatic irrigation system in the terrarium. Tests were conducted under several different environmental conditions to measure the system's response to changes in humidity and temperature. The research results show that the system is able to maintain terrarium humidity within optimal limits with a low error rate. The system is able to adjust control actions in real-time, produce consistent calculations, and provide humidity stability despite external changes.